Effects of Particle Combinations With Different Wettability on Foam Structure and Stability - Geng, Dianqiao; Li, Jiahui; Li, Huaying; Huang, Wenzhan (Frontiers in Materials, 2021)
Particle addition is an important method to prepare foam metal, and it is of great significance to clarify the mechanism of particle stabilizing liquid metal foam. In this paper, alcohol solution system is used to simulate liquid melt foam. By changing the wettability of particles to adjust the distribution position of particles in foam, two kinds of particles with different wettability are added, which are mixed and optimized in a certain proportion to improve the foam stability as much as possible. The main mechanism is that the large wetting angle particles at the gas-liquid interface to slow down the gas migration, while small wetting angle particles exist in the liquid film, which can reduce the liquid drainage velocity. The experimental results show that the effect of particle wettability on foam structure is greater than that on viscosity enhancement. The particles with large wetting angle are beneficial to the formation and stability of foam, and the particles with small wetting angle cannot stabilize the foam alone. The effect of two kinds of particle combinations with different wettability on foam stability is better than that of single kind of particle. Considering the height and uniformity of the foam structure, the optimal particle combination is finally obtained.